Analisis Faktor Demurrage, Dwelling Time Dan Human Resources Terhadap Waiting Time Pada PT. Putra Segara Abadi - Amalia Amalia; Dedy Rusmiyanto; Ratna Hidayati (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
The strategy of sea transportation in an effort to reduce logistics costs from the tugboat side so as to produce logistics costs that are able to create an increase in the competitiveness of national products. One of a series of services at the port, the implementation of pilotage services is one that is important to get attention because it is the first and last service provided to ships that will visit and depart from the port. Good management of tugboat services will help speed up ship services, maintain order, safety and security in the port environment, because when we talk about waiting time, we are talking about excess costs that will be incurred. This research is expected to see and learn about the loading and unloading system at PT. Putra Segara Abadi which focuses on what factors affect Waiting time which results in additional costs. The results showed that there was a positive and significant effect between Demurrage on Waiting Time (t count value of 2,013 > t table value of 1,98472), The results of the multiple linear regression equation showed that there was a positive and significant influence between Dwelling Time on Waiting Time (value t count of 2.289 > t table value of 1.98472), The results of the multiple linear regression equation indicate that there is a positive and significant influence between Human Resources on Waiting Time (t count value of 5.373 > t table value of 1.98472)